Comparison of the accuracy of immediate implant placement using static and dynamic computer-assisted implant system in the esthetic zone of the maxilla: a prospective study - Yuzhang Feng; Zhenya Su; Anchun Mo; Xingmei Yang (SpringerOpen, 2022)
Abstract Purpose This study aimed to compare the accuracy of fully guided between dynamic and static computer-assisted implant surgery (CAIS) systems for immediate implant placement in the esthetic zone. Methods A total of 40 qualified patients requiring immediate implant placement in the esthetic zone were randomly and equally assigned to either static CAIS group (n = 20) or dynamic CAIS groups (n = 20). Global deviations at entry, apex, and angular deviation between placed and planned implant position were measured and compared as primary outcomes. Secondary outcomes were the deviation of implant placement at mesial-distal, labial-palatal, and coronal-apical directions. Results For the immediate implant placement, the mean global entry deviations in static and dynamic CAIS groups were 0.99 ± 0.63 mm and 1.06 ± 0.55 mm (p = 0.659), while the mean global apex deviations were 1.50 ± 0.75 mm and 1.18 ± 0.53 mm (p = 0.231), respectively. The angular deviation in the static and dynamic CAIS group was 3.07 ± 2.18 degrees and 3.23 ± 1.67 degrees (p = 0.547). No significant differences were observed for the accuracy parameters of immediate implant placement between static and dynamic CAIS systems, except the deviation of the implant at entry in the labial-palatal direction in the dynamic CAIS group was significantly more labial than of the static CAIS (p = 0.005). Conclusions This study demonstrated that clinically acceptable accuracy of immediate implant placement could be achieved using static and dynamic CAIS systems. Trial registration ChiCTR, ChiCTR2200056321. Registered 3 February 2022, http://www.chictr.org.cn/showproj.aspx?proj=151348